COPD assessment test and severity of airflow limitation in patients with asthma, COPD, and asthma-COPD overlap syndrome - Kurashima, Kazuyoshi; Takaku, Yotaro; Ohta, Chie; Takayanagi, Noboru; Yanagisawa, Tsutomu; Sugita, Yutaka (International journal of chronic obstructive pulmonary disease, 2016)
The COPD assessment test (CAT) consists of eight nonspecific scores of quality of life. The aim of this study was to compare the health-related quality of life and severity of airflow limitation in patients with asthma, COPD, and asthma-COPD overlap syndrome (ACOS) using the CAT. We examined CAT and lung functions in 138 patients with asthma, 99 patients with COPD, 51 patients with ACOS, and 44 patients with chronic cough as a control. The CAT score was recorded in all subjects, and the asthma control test was also administered to patients with asthma and ACOS. The CAT scores were compared, and the relationships between the scores and lung function parameters were analyzed. The total CAT scores and scores for cough, phlegm, and dyspnea were higher in patients with ACOS than in patients with asthma and COPD. The total CAT scores were correlated with the percent predicted forced expiratory volume in 1 second only in patients with COPD. The total CAT scores and dyspnea scores adjusted by the percent predicted forced expiratory volume in 1 second were higher in patients with ACOS than in patients with COPD and asthma. The CAT scores and asthma control test scores were more closely correlated in patients with ACOS than in patients with asthma. Patients with ACOS have higher disease impacts and dyspnea sensation unproportional to the severity of airflow limitation.